2024
DOI: 10.1007/s00432-023-05537-w
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori upregulates circPGD and promotes development of gastric cancer

Wenjun Zhao,
Zhendong Yao,
Jia Cao
et al.

Abstract: Purpose Helicobacter pylori (H. pylori) has unique biochemical traits and pathogenic mechanisms, which make it a substantial cause of gastrointestinal cancers. Circular RNAs (circRNAs) have concurrently been identified as an important participating factor in the pathophysiology of several different cancers. However, the underlying processes and putative interactions between H. pylori and circRNAs have received very little attention. To address this issue, we explored the interaction between H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[23] For therapeutic intervention, CircPGD might be a promising new target. [24] One potential new target for GC therapy is lnc-PLCB1. [25] Table 2.…”
Section: Genetics Studies Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] For therapeutic intervention, CircPGD might be a promising new target. [24] One potential new target for GC therapy is lnc-PLCB1. [25] Table 2.…”
Section: Genetics Studies Referencesmentioning
confidence: 99%
“…H. pylori promoted cell migration and proliferation, boosted the inflammatory response, and inhibited apoptosis, which led to enhanced circPGD expression in infected human cells and three mechanisms that promoted GC spread. This finding suggested that H. pylori -related GC is influenced by CircPGD [ 24 ]. The formation of GCs is influenced by N6-methyladenosine (m6A) alterations and long noncoding RNAs (lncRNAs).…”
Section: Variable Genes and Hostsmentioning
confidence: 99%